The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/bit.26043
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐ethyloxazoline) as matrix for highly active electrospun enzymes in organic solvents

Abstract: Nanofibers are advantageous carriers for biocatalysts, because they show lower diffusion limitations due to their high surface/volume ratio. Only a few samples are known where enzymes are directly spun into nanofibers, mostly because there are not many suited polymer carriers. In this study, poly(2-ethyloxazoline) (PEtOx) was explored regarding its usefulness to activate various enzymes in organic solvents by directly electrospinning them from aqueous solutions containing the polymer. It was found that the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The literature data on the formation of non-woven fibrous mats based on POx is limited, and it mainly concerns the electrospinning of commercially available poly(2-ethyl-2-oxazoline) (PEtOx) of high molar mass and broad dispersity (Aquazol®) [38][39][40][41][42][43]. The first study on the optimisation of electrospinning conditions of an aqueous solution of PEtOx (M w of~500,000 g/mol) was described by Buruaga et al [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature data on the formation of non-woven fibrous mats based on POx is limited, and it mainly concerns the electrospinning of commercially available poly(2-ethyl-2-oxazoline) (PEtOx) of high molar mass and broad dispersity (Aquazol®) [38][39][40][41][42][43]. The first study on the optimisation of electrospinning conditions of an aqueous solution of PEtOx (M w of~500,000 g/mol) was described by Buruaga et al [38].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, George et al [39] obtained ultrafine fibres of cobalt oxide (Co 3 O 4 ) by combining the electrospinning method with high-temperature calcination from the precursor of PEtOx (M w of~500,000 g/mol)/cobalt acetate tetrahydrate in water. High molar mass PEtOx was also used as a potential carrier for the electrospinning of enzymes [40]. Optimisation of the process demonstrated that enzymes were more active after spinning with polymer than spinning alone.…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperatures of up to 60°C are possible, but the process becomes diffusion controlled and leads to inhomogeneously mineralized materials. Thus, the 400-500 lm thick films prepared in this work cannot be mineralized faster, but this might not be true for smaller structures, such as enzyme-loaded microparticles [55,56], fibers [57], or thin films [58], which might lead to new materials with interesting mechanical and optical properties. This will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…CT could be activated by a factor of up to 1,000 when solubilized by AOT in organic solvents (Paradkar & Dordick, ), while the activation of this enzyme immobilized on nanoporous silica glass in hexane reached a 110‐fold activity (P. Wang, Dai, Waezsada, Tsao, & Davison, ). CT entrapped in electrospun nanofibers was found to be 400 times more active than the suspended enzyme powder (Plothe et al, ). The best activation of CT found in this study was 250, which is in the order of magnitude of the best‐achieved activations of this enzyme.…”
Section: Discussionmentioning
confidence: 99%